2022
DOI: 10.3389/fsurg.2022.923949
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the Scene in Civilian Penetrating Brain Injury: Injury Type, Cause and Outcome in a Consecutive Patient Series in Austria

Abstract: BackgroundPenetrating brain injury (PBI) is a heterogeneous condition with many variables. Few data exist on civilian PBI. In some publications, PBI differentiation between low-velocity injury (LVI) and high-velocity injury (HVI) is made, but exact definitions are not given yet. The incidence of PBI depends heavily on the country of origin. Furthermore, captive bolt pistol (CBP) injuries represent a rare type of LVI and almost no reports exist in the human medical literature. Treatment of PBI has been controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…[2] In Austria, Marhold et al analyzed 27 patients with PTBI and concluded that initial GCS, trajectory, type of injury (low-or high-velocity), and pupil status are predictors of functional outcomes. [19] We have shown that the majority of our patients suffered from a stab wound which is a low-velocity penetrating object. Globally reported, non-missile low-velocity PTBI is a very rare condition.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[2] In Austria, Marhold et al analyzed 27 patients with PTBI and concluded that initial GCS, trajectory, type of injury (low-or high-velocity), and pupil status are predictors of functional outcomes. [19] We have shown that the majority of our patients suffered from a stab wound which is a low-velocity penetrating object. Globally reported, non-missile low-velocity PTBI is a very rare condition.…”
Section: Discussionmentioning
confidence: 70%
“…analyzed 27 patients with PTBI and concluded that initial GCS, trajectory, type of injury (low- or high-velocity), and pupil status are predictors of functional outcomes. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Based on the penetration speed, PBI can be divided into 2 categories, namely high-velocity penetration and low-velocity penetration. 13) This case is included in the category of low-velocity penetration. Preoperative planning is important t o determine the location of the foreign body and the extension of injury to the surrounding area.…”
Section: Discussionmentioning
confidence: 99%
“… 11 16) Impaired brain function can occur because of direct injury to the penetrating brain area or as an indirect result of vasospasm or multi-trauma injury from other locations. 2 5 7 13) The disturbances that occur can vary, for example in this case, the trajectory of the screwdriver penetrates through the white matter tract in the dominant frontal and temporal hemisphere areas, which can cause neurobehavioral disorders such as frontal lobe syndrome, cognitive impairment, sensory aphasia, hearing loss, and even hemiparesis. In our case, the patient did not experience any symptoms other than damage to the right eye.…”
Section: Discussionmentioning
confidence: 99%
“…Captive bolt gun (CBG) head injuries represent a rare form of penetrating brain injuries with only a few documented cases in the literature [1][2][3][4][5][6][7]. This is a device that is commonly employed in the meat industry to stun animals before slaughter [1,2]. A bolt penetrates the scull, causing direct and indirect injures to the brain parenchyma through bone fragments [1,2].…”
Section: Introductionmentioning
confidence: 99%